1993
DOI: 10.1093/nar/21.19.4483
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the regulation of the interferoninducible protein kinase PKR by Epstein - Barr virus RNAs EBER-1 and EBER-2 and adenovirus VA, RNA

Abstract: The interferon-inducible protein kinase PKR interacts with a number of small viral RNA species, including adenovirus VAI RNA and the Epstein-Barr virus-encoded RNA EBER-1. These RNAs bind to PKR and protect protein synthesis from inhibition by double-stranded RNA in the reticulocyte lysate system. Using a peptide phosphorylation assay we show here that EBER-1, like VAI, directly inhibits the activation of purified PKR. A second Epstein-Barr virus RNA, EBER-2, also regulates PKR. EBER-1, EBER-2 and VAI RNA exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
145
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(150 citation statements)
references
References 51 publications
3
145
0
2
Order By: Relevance
“…Lastly, most viruses studied to date block phosphorylation of eIF-2␣ by encoding proteins which bind double stranded RNA [e.g., E2L of vaccinia (22)(23)(24), 3 protein of Reo and rotaviruses (25)(26)(27)(28), and NS1 protein of influenza (29)], or proteins or RNA that inactivate PKR by binding to it [e.g., vaccinia K3L, Epstein-Barr virus EBERS 1 and 2 (30), adenovirus VA1 RNA (30,31), influenza virus-induced cellular p58 protein (32)], or degrade PKR [poliovirus (33)]. HIV-1 TAR sequence appears to bind to a cellular TAR binding protein and PKR (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, most viruses studied to date block phosphorylation of eIF-2␣ by encoding proteins which bind double stranded RNA [e.g., E2L of vaccinia (22)(23)(24), 3 protein of Reo and rotaviruses (25)(26)(27)(28), and NS1 protein of influenza (29)], or proteins or RNA that inactivate PKR by binding to it [e.g., vaccinia K3L, Epstein-Barr virus EBERS 1 and 2 (30), adenovirus VA1 RNA (30,31), influenza virus-induced cellular p58 protein (32)], or degrade PKR [poliovirus (33)]. HIV-1 TAR sequence appears to bind to a cellular TAR binding protein and PKR (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…EBER is a small RNA, is not transcribed into protein, and is known to bind some cellular proteins such as La, EAP/L22 and PKR . Among them, the association of EBER with PKR has been most intensively studied (Sharp et al, 1993;Yamamoto et al, 2000;Nanbo et al, 2002). We previously demonstrated that EBER binds PKR, inhibits its phosphorylation, and confers resistance to interferon-induced apoptosis (Nanbo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…As a countermeasure against the action of PKR, some viruses such as Epstein-Barr virus (EBV) constitutively express two ncRNAs, EBER1 and EBER2, which are 167 nt and 172 nt long, respectively. EBER1 has been previously demonstrated to bind to PKR and has been suggested to confer resistance to Fas-mediated apoptosis in tissue culture cells by blocking PKR activity (Clarke et al 1991;Sharp et al 1993;Nanbo et al 2005). EBER1 and EBER2 are the most abundant viral transcripts expressed during viral latency (∼5 × 10 6 per cell) and are predominantly localized in the nucleus (Lerner et al 1981;Howe and Steitz 1986;Fok et al 2006).…”
Section: Eber Rnasmentioning
confidence: 99%